Implementing holistic government : joined-up action on the ground - Wilkinson, David (Policy, 1999)
This report addresses the critical issues of implementation of the newly emerging and long-term public service agenda. The authors draw upon a unique range of research, practice and theory from the fields of community development, regeneration projects, public and private sector management and organisation development, as well as public and social policy.